2017
DOI: 10.1088/1361-6587/aa69e8
|View full text |Cite
|
Sign up to set email alerts
|

Outward particle transport by coherent mode in the H-mode pedestal in the Experimental Advanced Superconducting Tokamak (EAST)

Abstract: A coherent mode (CM) in the edge pedestal region has been observed on different fluctuation quantities, including density fluctuation, electron temperature fluctuation and magnetic fluctuation in H mode plasma on the Experimental Advanced Superconducting Tokamak (EAST) tokamak. Measurements at different poloidal positions show that the local poloidal wavenumber is smallest at the outboard midplane and will increase with poloidal angle. This poloidal asymmetry is consistent with the flute-like assumption (i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 33 publications
10
62
0
Order By: Relevance
“…This coherent fluctuation can be observed in all 11 channels of POINT diagnostics and in ECE channels in the pedestal region, indicating that the mode is located in the pedestal region. The toroidal mode number has been determined to be n = 15 by applying a similar method of analysis to that used in figure 3 of [31]. From this analysis, it is confirmed that the coherent fluctuation observed here is just the coherent mode (CM) presented in previous publications [30,31].…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…This coherent fluctuation can be observed in all 11 channels of POINT diagnostics and in ECE channels in the pedestal region, indicating that the mode is located in the pedestal region. The toroidal mode number has been determined to be n = 15 by applying a similar method of analysis to that used in figure 3 of [31]. From this analysis, it is confirmed that the coherent fluctuation observed here is just the coherent mode (CM) presented in previous publications [30,31].…”
Section: Resultssupporting
confidence: 68%
“…The toroidal mode number has been determined to be n = 15 by applying a similar method of analysis to that used in figure 3 of [31]. From this analysis, it is confirmed that the coherent fluctuation observed here is just the coherent mode (CM) presented in previous publications [30,31].…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The spectrum is dominated by a coherent mode (CM) after plasma enters the H-mode. This CM is in the pedestal region [11,12] and can be observed in all POINT channels. In order to extract the fluctuation amplitude, the fluctuation component of 10 kHz-35 kHz (δN el6, kHz ) is extracted from the original signal (δN el6 ) by applying a bandpass filter in this frequency range.…”
Section: Modulation Effects On Background Turbulencementioning
confidence: 71%
“…In experiment, it has been found that several turbulence modes in the ELM-free phase or inter-ELM phase are closely related to the pedestal transport [10][11][12][13][14][15][16][17][18][19][20][21][22]. In simulation, gyrokinetic codes found that several types of micro-turbulence, such as the micro-tearing mode (MTM) [23,24] and electron temperature gradient (ETG) mode [25], could be responsible for the pedestal transport.…”
Section: Nuclear Fusionmentioning
confidence: 99%